2008
DOI: 10.1136/jnnp.2007.120626
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue is associated with cerebral white matter hyperintensities in patients with systemic lupus erythematosus

Abstract: Increased cerebral WMH load is associated with increased fatigue, indicating a biological origin for some portion of fatigue in patients with SLE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 16 publications
3
35
1
Order By: Relevance
“…9,10 An association between distress and PTF is consistent with previous reports in the literature, 22,23 but those studies reported relationships between fatigue and distress measured concurrently following treatment infusions. With such associations, also found in the present study, causality cannot be determined.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…9,10 An association between distress and PTF is consistent with previous reports in the literature, 22,23 but those studies reported relationships between fatigue and distress measured concurrently following treatment infusions. With such associations, also found in the present study, causality cannot be determined.…”
Section: Discussionsupporting
confidence: 86%
“…N varies due to missing data. For reference, a recently published study 22 found that healthy adults whose levels of current fatigue were assessed using a VAS had a mean fatigue score of 19.7 (of a possible 100). In addition, using an identical VAS measure we have recently found mean distress levels of 38.2 in patients assessed in the clinic prior to breast surgery.…”
Section: Resultsmentioning
confidence: 99%
“…Only fatigue measured by VAS, not FSS, correlated with total WMH score. The authors concluded that fatigue is associated with a higher cerebral WMH load in SLE patients, supporting evidence for the biological explanation for fatigue in patients with chronic autoimmune diseases [107]. Another study utilized single-photon emission computed tomography imaging to investigate whether disturbances of cerebral blood flow (CBF) can be seen in SLE patients with fatigue.…”
Section: Measurements Of Fatiguementioning
confidence: 87%
“…did not find a significant association between infarcts seen on MRI to fatigue in SLE patients [83]. In another study by Harboe et al ., utilizing a semi-quantitative radiologic scale on a T2-weighted MRI study, noted that cerebral white matter hyperintensities (WMH), previously associated with cognitive impairment in multiple sclerosis, were also present in SLE patients [107]. The WMH changes are known to represent biochemical changes in brain tissue frequently seen in patients with SLE [80].…”
Section: Measurements Of Fatiguementioning
confidence: 99%
“…In our SLE sample, however, cognitive fatigue was not associated with Ch/Cr. Self-reported measures of general fatigue have been related to white matter hyperintensities in SLE and other disorders (Harboe et al, 2008; Schwid et al, 2003), but the relationship of general fatigue to cognitive fatigue is unclear. In our earlier work with SLE, self-reported fatigue was related to cognitive dysfunction only in patients who had overt neuropsychiatric manifestations (Kozora et al, 2006).…”
Section: Discussionmentioning
confidence: 99%